Career guidance conceptualization to improve career adaptability for generation z - Nadya, Aisha; Farozin, Muh (Universitas Negeri Yogyakarta, 2021)
Generation Z will control 20% of the workplace. Every generation has a different approach to work and the workplace. Z generation needs to have career adaptability to anticipate problems such as worries about not getting a job and a lack of understanding about the desired field of work. The research aims to explore and create a solid theoretical foundation for designing a career guidance model to increase the adaptability of Generation Z's career. The research uses library research methods sourced from books and literature on 1) career adaptability, 2) understanding generation Z, 3) counselling guidance models in the revolutionary era 4.0. The comparison between Generation Z characteristics and the dimensions of career adaptability, the primary need of Generation Z is career control. Career guidance services for Generation Z can be in the form of 1) coaching, 2) workshops, 3) inspirational content through social media, 4) internship programs.